Stress and coping among surgery residents in a developing country - Qamar Riaz; Syeda Kausar Ali; Muhammad Rizwan Khan; Abdul Rehman Alvi (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: Stress during residency training in surgical disciplines not only hampers professional development but can also compromise patient care and personal health. The purpose of this study was to measure the stress level among the surgical residents, identify factors within the learning and work environment that cause stress, and identify different strategies that the residents use habitually to cope with these stresses. Methods: This mix method study was conducted in the department of Surgery at Aga Khan University, Pakistan. Residents’ stress level was measured using Perceived Stress Scale (PSS); focus group discussions (FGDs) with faculty and residents explored stressors during residency training, while Brief COPE Inventory identified the residents’ preferred coping strategy. Results: A total of 68 (83%) surgery residents completed the survey of which 19% had high stress scores while only one resident had perception of low stress. Females had significantly higher stress scores (25.7±3.0; p=0.008) as compared to male counterparts. Planning (87.8%) and Self-distraction (65%) were the most commonly used adaptive and maladaptive strategies respectively. The reliability of the PSS and BCI measured by Cronbach’s alpha was 0.73 and 0.82 respectively. Work-life imbalance, workload and contradicting programme and hospital policies were identified in FGDs as major stressors during residency. Conclusion: Although surgical residency programmes are very stressful, coping strategies are not formally taught during surgical training. Academia and hospital should join hands in developing interventions to enable residents cope with the situation. Keywords: Stress level, Surgical Residency Training, Coping Strategies, Working hours